STRATEGI PENINGKATAN KAPASITAS PENYELENGGARAAN PEMERINTAHAN DAERAH - S.Sos, M.Si, Suryanto, (Pusat Pelatihan dan Pengambangan dan Kajian Desentralisasi dan Otonomi Daerah Lembaga Administrasi Negara, 2010)
This study attempts to identify capacity building efforts conducted by local governments, obstacles facing local govenments in those efforts, as well as formulating models/strategies for effective local govenment capacity building. This study utilizes primary data pertain to local government capacity building(CB) implementation and publicly available data on CB model/strategy as secondary data. As approach of this study, qualitative analysis was based onindepth interview, discussion, and literature study. The reseacrh reveals that CB activities had been conducted by local govenment (partially). Yet, the activitieswere not based on comprehensive evaluation. It is recommended that local govenment utilize CB models/strategies that have been developed from the study